Factors Influencing Intrauterine Contraceptive Device Uptake - Amra, Ricca Nophia; Rambe, Rizka Sititah; Bancin, Fitriani (Journal of Maternal and Child Health, 2023)
Background: The Intrauterine Contraceptive Device (IUD) is an effective long-term reversible contraceptive method suitable for women of reproductive age. However, its uptake is low in Aceh province, Indonesia. This study aimed to analyze factors influencing IUD uptake among women of reproductive age in Aceh. Subjects and Method: This was a case control study conducted at the Simpang Kiri Health Center, Subulussalam, Aceh from January to June, 2023. A total of 106 women of reproductive age were selected for this study. The dependent variable was IUD uptake. The independent variables were age, education, knowledge, parity, attitudes, sociodemographic variable, and the role of health personnel. Data on IUD uptake were obtained from medical records in Subulussalam District Health Office and the Simpang Kiri Health Center, in Aceh. The other data were collected by questionnaire and observation. The data were analyzed by multiple logistic regression. Results: Factors increasing the IUD uptake in women of reproductive age were good knowledge (OR= 11.11; 95% CI= 3.29 to 37.58; p<0.001) and the active role of health personnel (OR= 8.36; 95% CI= 2.73 to 25.61; p <0.001). Positive attitude increased IUD uptake, but it was statistically non-significant (OR= 1.26; 95% CI= 0.39 to 3.97; p=0.697). Conclusion: Factors increasing the IUD uptake in women of reproductive age are good knowledge and the active role of health personnel. Positive attitude increases IUD uptake, but it is statistically non-significant. Keywords: intrauterine contraceptive device, case control, reproductive. Correspondence: Ricca Nophia Amra. Midwifery Academy of Medica Bakti Persada. Jl. Pinang Baris Desa Lae Oram Dusun Indah No. 193, Simpang Kiri, Subulussalam, 24781, Aceh, Indonesia. Email: ricca.ubudiyah@gmail.com. Mobile: 082294425839.